Prevalence and orthodontic management of missing permanent maxillary lateral incisor at a referral centre in Sabah - Lee, Jin Han (IIUM Journal of Orofacial and Health Sciences, 2023)
This was a cross-sectional study of the prevalence and orthodontic management of developmental missing permanent maxillary lateral incisor of patients referred for orthodontic treatment from year 2010 to 2020. The dental records of written case notes, radiographs, and study models that fulfilled the inclusion criteria were selected using systematic sampling and were assessed retrospectively. Sample were taken from every five dental records. Dental records that did not fulfil the inclusion criteria were substituted. Data taken were the demographic data, side of the missing maxillary lateral incisor, and the orthodontic management. All variables were analysed descriptively. The differences between orthodontic open space and orthodontic close space with respect of unilateral and bilateral missing permanent maxillary lateral incisor were tested using Fisher’s exact test. From the total of 291 samples, there were 11 (3.78%) patients presented with missing permanent maxillary lateral incisor. The mean age of the patients was 17.46 ± 1.52 years. All 11 patients were females. There were six (54.55%) patients presented with bilateral missing permanent maxillary lateral incisor, while five (45.45%) were unilateral. From the unilateral group, there were three (27.27%) patients presented with right side missing permanent maxillary lateral incisor. Six (54.55%) patients were treated with orthodontic open space, while five (45.45%) patients were treated with orthodontic close space. In conclusion, the prevalence of missing permanent maxillary lateral incisor was 3.78%. All patients were females. More patients presented with bilateral missing permanent maxillary lateral incisor. The treatments provided were orthodontic open space and orthodontic close space.